Analisis Penggunaan Media Gambar dalam Menulis Puisi Siswa Kelas X IPS 3 SMA Negeri 1 Lotu - Agusman Halawa; Jerni Natalina Zebua; Mira Krisdayanti Gea; Arozatulo Bawamenewi (Journal on Education, 2023)
Analysis of the use of media images in writing poetry with qualitative methods with observation, test and interview techniques. This research was conducted on class X IPS 3 SMA Negeri 1 Lotu. The formulation of the problem in this study is how the effectiveness of media images in writing poetry and how students are able to write poetry using media images. The purpose of this study was to determine the effectiveness of media images in writing poetry and to determine students' ability to write poetry using media images. The results of the study show that the use of media images can generate desire, motivation, stimulation and generate ideas for students in writing poetry, besides that it is also able to attract students' interest and provide good skills in writing poetry.